Complex multi–fuzzy subgroups. (17th November 2022) - Alsarahead, Mikhled Okleh; Al-Husban, Abdallah
Abstract: There has been an increased recognition that more attention needs to be paid to the area of fuzzy algebra. A closer look at the literature, reveals several gaps and shortcomings such as the concept of complex multi-fuzzy subgroups. This article introduces the concept as well as investigates the nexus between complex multi-fuzzy subgroups and multi-fuzzy subgroups. Further, this article discovers that each complex multi-fuzzy subgroup produces two multi-fuzzy subgroups. Furthermore, there is additional discussion of the nexus between complex multi-fuzzy subgroups and classical subgroups. Finally, characterizes and illustrates the back-and-forth images carried by such a group homomorphism.